Calcium Signaling in Plant-Insect Interactions - Ambra S. Parmagnani; Massimo E. Maffei (Plants, 2022)
In plant–insect interactions, calcium (Ca2+) variations are among the earliest events associated with the plant perception of biotic stress. Upon herbivory, Ca2+ waves travel long distances to transmit and convert the local signal to a systemic defense program. Reactive oxygen species (ROS), Ca2+ and electrical signaling are interlinked to form a network supporting rapid signal transmission, whereas the Ca2+ message is decoded and relayed by Ca2+-binding proteins (including calmodulin, Ca2+-dependent protein kinases, annexins and calcineurin B-like proteins). Monitoring the generation of Ca2+ signals at the whole plant or cell level and their long-distance propagation during biotic interactions requires innovative imaging techniques based on sensitive sensors and using genetically encoded indicators. This review summarizes the recent advances in Ca2+ signaling upon herbivory and reviews the most recent Ca2+ imaging techniques and methods.